The effect of information technology, adherence to accounting rules, and human resources on the reliability of financial statements in Central Lombok District Government - Hernawan Ardiyanto; Hermanto .; Ni Ketut Surasni (The Indonesian Accounting Review, 2016)
This study aims to determine the effect of information technology, adherence to accounting rules, and human resources to the reliability of financial statements in Central Lombok District Government. This study uses a quantitative approach, with primary data obtained through questionnaires. The respondents are the employees of finance department of Cen-tral Lombok District Government. The independent variables used in this study are infor-mation technology, adherence to accounting rules, and human resources, while the depen-dent variable is the reliability of financial statements. The respondents are asked to answer a set of questions listed in a questionnaire. 72 samples are taken from the total population of 256, however only 63, which are considered valid to be analyzed. For the data analysis, it used double linear regression method and processed by using SPSS 18.0. The data analysis results based on t-test show that information technology and human resources have positive significant effect on the reliability of financial statements, but adherence to accounting rules has positive insignificant effect on the reliability of financial statements in Central Lombok District Government. The implication of this study leads to the importance of the optimized preparation of financial statements to achieve the reliable financial statements.